2017
DOI: 10.1021/acsmacrolett.7b00262
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tailored Dispersity on the Self-Assembly of Dimethylsiloxane–Methyl Methacrylate Block Co-Oligomers

Abstract: The effect of dispersity on block polymer selfassembly was studied in the monodisperse limit using a combination of synthetic chemistry, matrix-assisted laser desorption ionization spectroscopy, and small-angle X-ray scattering. Oligo-(methyl methacrylate) (oligoMMA) and oligo(dimethylsiloxane) (oligoDMS) homopolymers were synthesized by conventional polymerization techniques and purified to generate an array of discrete, semidiscrete, and disperse building blocks. Coupling reactions afforded oligo(DMS−MMA) bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
99
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 39 publications
2
99
1
Order By: Relevance
“…The bulk phase behavior of alt/alt-32B resembles recent studies from Zuckermann and coworkers on polypeptoid self-assembly where side-chain crystallization, rather than bulk phase separation, leads to lamellae with small domain spacings. 5c, 8a Similarly, Meijer and co-workers recently reported on oligodimethylsiloxane- b -oligo(L)lactides that crystallize and assemble into lamellae. 8d, 15 Here again, our results show how stereochemistry can lead to dramatic changes in DPT assembly, switching from crystalline to amorphous materials.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The bulk phase behavior of alt/alt-32B resembles recent studies from Zuckermann and coworkers on polypeptoid self-assembly where side-chain crystallization, rather than bulk phase separation, leads to lamellae with small domain spacings. 5c, 8a Similarly, Meijer and co-workers recently reported on oligodimethylsiloxane- b -oligo(L)lactides that crystallize and assemble into lamellae. 8d, 15 Here again, our results show how stereochemistry can lead to dramatic changes in DPT assembly, switching from crystalline to amorphous materials.…”
mentioning
confidence: 96%
“…Despite these advances, the role of stereochemistry in uniform macromolecular systems has received relatively little attention. For example, though the composition, sequence, and dispersity of diblock co-oligomers/polymers have been investigated recently, 8 the role of stereochemistry in uniform block copolymer assembly has not, to our knowledge, been systematically studied. A robust strategy for the synthesis of stereochemically pure block copolymers with absolute structural control is a prerequisite for such an endeavor.…”
mentioning
confidence: 99%
“…As oligomers synthesized via radical polymerization are often polydisperse in nature, a novel strategy to prepare discrete oligomeric library with acrylates, styrenic, siloxanes as well as conjugated oligomers was developed using automated flash chromatography (181,182). This strategy allowed for preparation of discrete oligomers with distributions close to unity which provided an opportunity to study self-assembly of triplex helix stereocomplex of PMMA oligomers (183) and also dispersity effects on the self-assembly of oligomer composed of dimethylsiloxane-block-methyl methacrylate (184).…”
Section: Sequence Defined Oligomersmentioning
confidence: 99%
“…The block copolymer of butadiene with octamethylcyclotetrasiloxane (PB‐b‐PDMS) initiated by n‐butyllithium carries not only residual double bonds but also siloxane groups. In this contribution, we described here a novel strategy to prepare graft‐modified 1,2‐PB by Mo‐based coordinative polymerization of PB‐b‐PDMS and butadiene.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work showed that the residual double bond in polybutadiene-acrylonitrile copolymer (PB-b-NBR) could further polymerize with Bd monomers via the Mo-based catalyst to prepare graft-modified 1,2-PB. 28 The block copolymer of butadiene with octamethyl cyclotetrasiloxane (PB-b-PDMS) [29][30][31][32][33][34] initiated by n-butyllithium carries not only residual double bonds but also siloxane groups. In this contribution, we described here a novel strategy to prepare graft-modified 1,2-PB by Mo-based coordinative polymerization of PB-b-PDMS and butadiene.…”
Section: Introductionmentioning
confidence: 99%